2019
DOI: 10.5603/gp.2019.0064
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sclerostin levels in relation to nutritional status, sex hormones and selected bone turnover biochemical markers levels in peri- and postmenopausal women

Abstract: Objectives:Hormonal changes during the peri-and postmenopausal age, especially decreasing estradiol levels as the result of the expired ovarian function, are an established link of the pathogenesis of postmenopausal osteoporosis. The objective of the study was to examine the association between the circulating sclerostin levels and nutritional status, sex hormones and selected bone markers turnover levels in peri-and postmenopausal women. Material and methods:The study enrolled 84 stable-body mass women (31 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In kidney transplant recipients, a positive correlation between sclerostin and vitamin D has been found [27]. Nevertheless, in this study in line with a recent investigation of perimenopausal and postmenopausal women [28] no correlation between vitamin D and bioactive sclerostin levels could be detected. Median values of all bone turnover markers were within the normal range.…”
Section: Discussionsupporting
confidence: 67%
“…In kidney transplant recipients, a positive correlation between sclerostin and vitamin D has been found [27]. Nevertheless, in this study in line with a recent investigation of perimenopausal and postmenopausal women [28] no correlation between vitamin D and bioactive sclerostin levels could be detected. Median values of all bone turnover markers were within the normal range.…”
Section: Discussionsupporting
confidence: 67%
“…Our data are in accordance with previous studies which showed higher serum CTX levels in osteoporotic patients than in non-osteoporosis groups 38 39 . Serum CTX levels are negatively correlated with estrone levels in males and positively correlated with SHBG levels in peri- and postmenopausal women with osteoporosis 40 41 , suggesting a close relationship between the level of BTMs and sex hormones.…”
Section: Discussionmentioning
confidence: 97%
“…This protein is already a documented inhibitor of osteoblast proliferation and differentiation, which can lead to bone demineralization [46]. Studies have suggested that one of the important factors that lead to an increase in sclerostin secretion is fluctuations in estrogen concentrations and deficiency, as well as a reduction in bone loading (mechanical stress), leading to a significant loss of bone mass [47,48]. It has also been noted that when thyroid hormone concentrations fluctuate (e.g., thyroid hormone excess), sclerostin levels are high, and after treatment of thyrotoxicosis, sclerostin concentrations decrease [49,50].…”
Section: Discussionmentioning
confidence: 99%